2019
DOI: 10.1007/s10584-019-02450-5
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate warming, cultivar shifts, and phenological dates on rice growth period length in China after correction for seasonal shift effects

Abstract: Crop phenology changes are important indicators of climate change. Climate change impacts on crop phenology are generally investigated through statistical analysis of the relationship between growth period length and growth period mean temperature. However, growth periods may be either earlier or later in a given year; hence, changes in mean temperature indicate both the effects of climate change and those attributable to seasonal temperature differences. Failure to consider temperature change resulting from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The above results show that in addition to changes in T during the growth period have an important impact on crop phenology, AP and AS also have a greater impacts on crop phenology (He et al, 2020;Liu et al, 2021). The previous studies often only considered the impact of climate warming on crop phenology, and ignored the impact of AP and AS on crop phenology (Wang et al, 2013;Xiao et al, 2015;Zhao et al, 2015;Mo et al, 2016;Xiao et al, 2017;Ye et al, 2019). Therefore, in the future, we should fully consider the impact of different climate variables on crop phenology in order to more clearly understand the impact mechanism of climate change on crop phenology (Bai and Xiao, 2020).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…The above results show that in addition to changes in T during the growth period have an important impact on crop phenology, AP and AS also have a greater impacts on crop phenology (He et al, 2020;Liu et al, 2021). The previous studies often only considered the impact of climate warming on crop phenology, and ignored the impact of AP and AS on crop phenology (Wang et al, 2013;Xiao et al, 2015;Zhao et al, 2015;Mo et al, 2016;Xiao et al, 2017;Ye et al, 2019). Therefore, in the future, we should fully consider the impact of different climate variables on crop phenology in order to more clearly understand the impact mechanism of climate change on crop phenology (Bai and Xiao, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…To some extent, adopting reasonable management measures is an effective way to deal with climate change (Wang et al, 2013;He et al, 2020). Related studies pointed out that delaying sowing dates and applying the longer-duration cultivar were management adaptations used by farmers to adapt to climate change occurring in the past few decades, and that can continue to be used (Wang et al, 2013;Tao et al, 2014a;Zhao et al, 2015;Wang et al, 2017a;Xiao et al, 2017;Xiao et al, 2019;Ye et al, 2019). With the climate warming, the potential growing season has lengthened, and the risk of low-temperature freezes and frost injury has decreased in NEC (Gong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses we found were in agreement with climate change responses reported by others. For example, Ye et al [71] reported that the rice growing season length was reduced by 3.1 days per 1°C increase temperature in a single rice system in China. Zhang et al [72] reported that growth duration length could be shortened by 3.0 days°C −1 from emergence to heading, and 1.1 days°C −1 from heading to maturity and 4.4 days −1 from emergence to maturity.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on climate change impacts on the yields of major annual cereal crops such as rice, wheat, corn, soybean, and maize (Luo et al, 2005;Kucharik and Serbin, 2008;Xiong et al, 2009;Jing et al, 2012;Ye et al, 2019). However, to date, comprehensive assessments of climate change impacts on perennial crops (e.g., the tea plant) are rare.…”
Section: Introductionmentioning
confidence: 99%